Development of Processes for Recombinant L-Asparaginase II Production by Escherichia coli Bl21 (De3): From Shaker to Bioreactors - Thaís Barros; Larissa Brumano; Marcela Freitas; Adalberto Pessoa; Nádia Parachin; Pérola O. Magalhães (MDPI AG, 2020)
Since 1961, L-asparaginase has been used to treat patients with acute lymphocytic leukemia. It rapidly depletes the plasma asparagine and deprives the blood cells of this circulating amino acid, essential for the metabolic cycles of cells. In the search for viable alternatives to produce L-asparaginase, this work aimed to produce this enzyme from Escherichia coli in a shaker and in a 3 L bioreactor. Three culture media were tested: defined, semi-defined and complex medium. L-asparaginase activity was quantified using the β-hydroxamate aspartic acid method. The defined medium provided the highest L-asparaginase activity. In induction studies, two inducers, lactose and its analog IPTG, were compared. Lactose was chosen as an inducer for the experiments conducted in the bioreactor due to its natural source, lower cost and lower toxicity. Batch and fed-batch cultures were carried out to reach high cell density and then start the induction. Batch cultivation provided a final cell concentration of 11 g L−1 and fed-batch cultivation produced 69.90 g L−1 of cells, which produced a volumetric activity of 43,954.79 U L−1 after lactose induction. L-asparaginase was produced in a shaker and scaled up to a bioreactor, increasing 23-fold the cell concentration and thus, the enzyme productivity.